KEPEMIMPINAN ELI SEBAGAI PRAKTIK KEKUASAAN RELASIONAL: SEBUAH KRITIK FOUCAULTIAN TERHADAP NEPOTISME - Wira Adi, Willy Etantri; Martinus, Patrick; Setianingrum, Erna (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2026)
Relational leadership, which emphasizes proximity and trust, frequently serves as a gateway for nepotistic practices, particularly within community-based organizations such as churches. This article aims to analyze the leadership of Eli the Priest (1 Samuel 2–4) through the lens of Michel Foucault's relational power theory to uncover the mechanisms of social nepotism concealed within religious authority structures. This study employs a qualitative hermeneutic approach alongside critical discourse analysis, utilizing the biblical text as primary data and literature on nepotism and power theory as secondary data. The findings indicate that Eli's leadership failure was not merely an individual moral failing, but rather the product of a relational power network that positioned his sons as an inner circle, thereby normalizing deviance and hindering accountability. The Foucaultian analysis reveals how pastoral power can be distorted into an instrument of domination through relational closeness. This article contributes to the discourse on Christian leadership by introducing a critical-sociological perspective to diagnose the pathology of relational nepotism, while also offering a prevention framework based on accountability and transparency systems. The results of this research are highly relevant for both religious and secular organizations in managing the risks associated with the abuse of power through inner circles.